2009
DOI: 10.1155/2009/173439
|View full text |Cite
|
Sign up to set email alerts
|

Expansion ofCD8+CD57+T Cells in an Immunocompetent Patient with Acute Toxoplasmosis

Abstract: CD57+ T cells increase in several viral infections like cytomegalovirus, herpesvirus, parvovirus, HIV and hepatitis C virus and are associated with several clinical conditions related to immune dysfunction and ageing. We report for the first time an expansion of CD8+ CD57+ T cells in a young patient with an acute infection with Toxoplasma gondii. Our report supports the concept that CD8+ CD57+ T cells could be important in the control of chronic phase of intracellular microorganisms and that the high numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…However, certain subpopulations of the tissue-infiltrating memory/effector T cells express homing receptors, which target their infiltration of injured tissues through activated endothelial cells even in the absence of a specific target antigen (22). These T cell subsets have the ability, without the need of antigenpresenting cells, to directly recognize products of stressed cells through their receptors and are up-regulated in chronic immune activation states (23)(24)(25)(26). In particular, the frequency of terminally differentiated CD8 + effector memory T (T EMRA ) cells (CD3 + CD8 + CD11a ++ CD28 − CD57 + T cells) is driven by chronic antigen exposure and correlates with aging of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…However, certain subpopulations of the tissue-infiltrating memory/effector T cells express homing receptors, which target their infiltration of injured tissues through activated endothelial cells even in the absence of a specific target antigen (22). These T cell subsets have the ability, without the need of antigenpresenting cells, to directly recognize products of stressed cells through their receptors and are up-regulated in chronic immune activation states (23)(24)(25)(26). In particular, the frequency of terminally differentiated CD8 + effector memory T (T EMRA ) cells (CD3 + CD8 + CD11a ++ CD28 − CD57 + T cells) is driven by chronic antigen exposure and correlates with aging of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that CD8 + CD57 + Tcells were expanded in an immunocompetent patient with acute toxoplasmosis 30 . As these T cells produce large amounts of IFN‐γ and IL‐5 (which are crucial in the immune response against Toxoplasma gondii ), it is possible that cytotoxic CD8 + CD57 + cells can prevent the reactivation of T. gondii in a similar manner because they control HCMV reactivation throughout a lifetime 30 …”
Section: Cd8+ Cd28− (Cd8+ Cd57+) T Cells In Health and Diseasementioning
confidence: 96%
“…Various authors describe CD8 + CD28 − T cells as either immunosuppressive 56–61 or cytotoxic, 2,62–65 whereas CD8 + CD57 + T cells in the majority of cases are described as highly cytotoxic 10,30–32,66,67 . It was also shown that CD57 expression strongly correlates with simultaneous expression of granzymes and perforin in CD8 + T cells 68 .…”
Section: Cd8+ Cd28− (Cd8+ Cd57+) T‐cell Subsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic viral infections such as HCMV ( 104 ), human immunodeficiency virus (HIV) ( 105 ), hepatitis C virus ( 106 ), and Epstein–Barr virus (EBV) ( 107 ) infections offer some of the clearest examples of expansion of CD57 + CD8 + T cells, presumably as a result of persistent antigenic stimulation, and increased proportions of CD57 + CD8 + T cells have also been reported in those infected with human parvovirus ( 108 ), measles ( 109 ), pulmonary tuberculosis ( 92 ), and toxoplasmosis ( 93 ). The majority of these CD57 + CD8 + T cells, at least in HCMV infection, appear to be antigen-specific and their presence is associated with a low incidence of reactivation ( 94 , 95 ).…”
Section: Cd57 Expression During Infectionmentioning
confidence: 99%